One Mind: How Our Individual Mind Is Part of a Greater Consciousness and Why It Matters by Larry Dossey - Alexander, John B. (Journal of Scientific Exploration, 2016)
One Mind brings age-old philosophies into immediate focus, and more importantly illuminates the current context in a world dominated by a materialistic view of everything. In Recovering the Soul, written in 1989, Dossey created the term nonlocal mind, what he states “is a spatially and temporally infinite aspect of our consciousness.” Nonlocal mind, he suggests, is analogous to what has been described as the soul; a concept often rejected by traditional scientists. There is an inherent conflict between a materialistic worldview and a concept of a consciousness-based, infinite interconnectedness, and the implications could not be more profound. If Dossey is correct, and everything is interconnected at some fundamental level, and I certainly believe he is, then it should impact all aspects of our daily lives. Understanding that the hurtful actions we often take against others also are harmful to ourselves and everyone else, while far from new, is mostly lost in our day-to-day lives. He argues that it shouldn’t be. One Mind is oriented toward the layperson but will still be of interest to researchers such as most SSE members. The author is well-known to the SSE, and a frequent contributor at our conferences. Dossey is the author of many books on the power of mind and alternative healing methodologies, including the classic Space, Time & Medicine published in 1982. As an internal medicine physician, he is exceptionally well-qualified to address the complex and not-well-understood issues of the impact the mind has on health. Previously he served as the chief-of-staff of Medical City Dallas Hospital, and he had extensive experience with traumatic injuries as a combat doctor assigned to the U.S. Army 173rd Airborne Brigade in Vietnam.